PERBEDAAN TINGKAT KECUKUPAN ENERGI DAN AKTIVITAS FISIK PADA REMAJA DOWN SYNDROME OVERWEIGHT DAN NONOVERWEIGHT[Comparison of Energy Adequacy Level and Physical Activity of Overweight and NonOverweight Adolescence with Down Syndrome] - Diana Rizqi Fauziyah; R. Bambang Wirjatmadi (Universitas Airlangga, 2019)
Overweight and obesity are nutritional problems that are often found in adolescence and early adulthood who experience down syndrome. The purpose of this research was to compare the energy adequacy level and physical activity of overweight and non-overweight adolescene with down syndrome. This research used case control study design. Collected data included antropomethry data, energy intake with 2x24 hours food recall, and pyhsical activity with physical activity questionnaire. Data were analyzed using Mann Whitney test. This research showed that adolescents with down syndrome tend to had low energy intake and activity level. There was no signifi cant difference in evergy adequacy level (p value=0.571) and physical activity level in both groups (p value=0.182).